Peculiarities of the National Police personnel participation in combat operations - I. V. Vlasenko; V. V. Fedorov; F. F. Zurov (Law and Safety)
The full-scale war in Ukraine has been going on for three years now, and the Russian army is facing steady resistance from the Ukrainian Armed Forces. The law enforcement forces cannot help but take part in hostilities in the course of their direct duties. Law enforcement officers are disciplined, trained, have certain knowledge of combat tactics, and are armed, so they can help effectively in confronting the enemy.